Preparing Leadership, Innovation and Change for 21st Century: Lessons from National Proffesional Bodies - Sam, Man Keong; Soong, Cai Juan (INTI International University, 2018)
It is challenging and tedious in managing a non-profit organization (NPO) due to the constantly changing world especially in the 21st century. Data and information were collected via desktop studies and active participation from three NPOs. The history, organizational structure, development, and the changes from these three NPOs were studied. Good lessons were learnt about good leadership for the survival, success and sustainability from these three NPOs. Thus, based on this premise, two new models are developed, and it convinced us that these crucial information and lessons can be right guidance and assistance to unlock frontiers for preparing leadership, innovation and change in 21st century for national professional bodies.